Therapy Dogs as a Crisis Intervention After Traumatic Events? – An Experimental Study - Lass-Hennemann, Johanna; Schäfer, Sarah K.; Römer, Sonja; Holz, Elena; Streb, Markus; Michael, Tanja (Frontiers in Psychology, 2018)
Abstract Animal-assisted therapy has been proposed as a treatment adjunct for traumatized patients. In animal-assisted crisis response, dogs are used directly after a traumatic event to reduce stress and anxiety. However, to date there are few controlled studies investigating the effects of therapy dogs on PTSD symptoms and to our knowledge there is no study investigating the effects of a therapy dog intervention directly after a traumatic event. In this study, 60 healthy female participants were randomly assigned to one of three groups: After exposure to a “traumatic” film clip (trauma-film paradigm), one group of participants interacted with a friendly dog for 15 minutes, another group of participants watched a film clip showing a person interacting with a friendly dog and the last group was instructed to relax. Participants who had interacted with the dog after the film reported lower anxiety levels, less negative affect, and more positive affect after the intervention as compared to the other two groups. However, the participants who interacted with the dog showed less decrease in physiological arousal after the traumatic film clip compared to both other groups. There were no differences in intrusion symptoms between the three groups. Our results show that dogs are able to lessen subjectively experienced stress and anxiety after a “traumatic” stress situation.